Identification and characterization of a novel promoter for the human ANO1 gene regulated by the transcription factor signal transducer and activator of transcription 6 (STAT6). Issue 1 (28th October 2014) - Mazzone, Amelia; Gibbons, Simon J.; Bernard, Cheryl E.; Nowsheen, Somaira; Middha, Sumit; Almada, Luciana L.; Ordog, Tamas; Kendrick, Michael L.; Lombardo, KMarie Reid; Shen, K. Robert; Galietta, Luis J. V.; Fernandez‐Zapico, Martin E.; et al.
Abstract : Anoctamin‐1 (Ano1) is a widely expressed protein responsible for endogenous Ca 2+ ‐activated Cl 2 currents. Ano1 is overexpressed in cancer. Differential expression of transcriptional variants is also found in other diseases. However, the mechanisms underlying regulation of Ano1 are unknown. This study identifies the Ano1 promoter and defines a mechanism for regulating its expression. Next‐generation RNA sequencing (RNA‐seq) analysis in human gastric muscle found a new exon upstream of the reported exon 1 and identified a promoter proximal to this new exon. Reporter assays in human embryonic kidney 293 cells showed a 6.7 ± 2.1fold increase in activity over empty vector. Treatment with a known regulator of Ano1 expression, IL‐4, increased promoter activity by 1.6 ± 0.02‐fold over untreated cells. The promoter region contained putative binding sites for multiple transcription factors including signal transducer and activator of transcription 6 (STAT6), a downstream effector of IL‐4. Chromatin immunoprecipitation (ChIP) experiments on T84 cells, which endogenously express Ano1, showed a 2.1 ± 0.12‐fold increase in binding of STAT6 to P0 after IL‐4 treatment. These results were confirmed by mutagenesis, expression, and RNA interference techniques. This work allows deeper understanding of the regulation of Ano1 in physiology and as a potential therapeutic target in a variety of diseases—Mazzone, A., Gibbons, S. J., Bernard, C. E., Nowsheen, S., Middha, S., Almada, L. L., Ordog, T., Kendrick, M. L., Reid Lombardo, KM., Shen, K. R., Galietta, L. J. V., Fernandez‐Zapico, M. E., and Farrugia, G., Identification and characterization of a novel promoter for the human ANO1 gene regulated by the transcription factor signal transducer and activator of transcription 6 (STAT6). FASEB J. 29, 152–163 (2015). www.fasebj.org